MRNA and small RNA gene expression changes in peripheral blood to detect internal Ra-223 exposure. (4th May 2022) - Ostheim, Patrick; Miederer, Matthias; Schreckenberger, Mathias; Nestler, Tim; Hoffmann, Manuela A.; Lassmann, Michael; Eberlein, Uta; Barsegian, Vahe; Rump, Alexis; Majewski, Mattháus; Port, Matthias; Abend, Michael
Abstract: Purpose: Excretion analysis is the established method for detection of incorporated alpha-emitting radionuclides, but it is laborious and time consuming. We sought a simplified method in which changes in gene expression might be measured in human peripheral blood to detect incorporated radionuclides. Such an approach could be used to quickly determine internal exposure in instances of a radiological dispersal device or a radiation accident. Materials and methods: We evaluated whole blood samples from five patients with castration-resistant prostate cancer and multiple bone metastases (without visceral or nodal involvement), who underwent treatment with the alpha emitting isotope Radium-223 dichloride (Ra-223, Xofigo ® ). Patients received about 4 MBq per cycle and, depending on survival and treatment tolerance, were followed for six months. We collected 24 blood samples approximately monthly corresponding to treatment cycle. Results: Firstly, we conducted whole genome screening of mRNAs (mRNA seq) and small RNAs (small RNA seq) using next generation sequencing in one patient at eight different time points during all six cycles of Ra-223-therapy. We identified 1900 mRNAs and 972 small RNAs (222 miRNAs) that were differentially up- or down-regulated during follow-up after the first treatment with Ra-223. Overall candidate RNA species inclusion criteria were a general (≥|2|-fold) change or with peaking profiles (≥|5|-fold) at specific points in time. Next we chose 72 candidate mRNAs and 101 small RNAs (comprising 29 miRNAs) for methodologic ( n = 8 samples, one patient) and independent ( n = 16 samples, four patients) validation by qRT-PCR. In total, 15 mRNAs (but no small RNAs) were validated by methodologic and independent testing. However, the deregulation occurred at different time points, showing a large inter-individual variability in response among patients. Conclusions: This proof of concept provides support for the applicability of gene expression measurements to detect internalized alpha-emitting radionuclides, but further work is needed with a larger sample size. While our approach has merit for internal deposition monitoring, it was complicated by the severe clinical condition of the patients we studied.